Isolation and identification of Aeromonas hydrophila from Liza aurata and study the effect of antibiotics. (Latakia University Journal -Biological Sciences Series, 2024)
This research was conducted to isolate Aeromonas hydrophila from Liza aurata . Where 20 samples were collected from marine waters at the Assaid and Annozha port site (which is considered a polluted area) during the summer and winter seasons of 2019/2020. Height and weight were measured and sex was determined, in addition to microbiological study of the intestines, gills and liver      The results showed that the Aeromonas hydrophila isolates were round in shape, medium and small, with a domed edge, and their color ranged from pale white to pink.     The results showed that the A.hydrophila isolates showed the highest sensitivity to Chloramphenicol, while they were resistant to ampicillin.